Comparing the Effect of the Corrective Exercises of America's National Academy of Sports Medicine and Pilates on the Correction of Lordosis among Female High School Students in Golestan Province in 2018 - Hadiseh Okhli; Hamid Hojjati; Golbahar Akhoundzadeh (Shiraz University of Medical Sciences, 2019)
Background: Lordosis is a curvature in the posterior of vertebral column. Loss of normal lordotic alignment may induce pathologic changes in the spine from load bearing and accelerate degeneration of the functional motion units. The purpose of this study was to compare the effect of the corrective exercises of the National Academy of Sports Medicine (NASM) and Pilates on the correction of lumbar lordosis among female high school students. Methods: In this experimental study, conducted in 2018, 45 female high school students suffering from lumbar lordosis were randomly selected from Golestan Province and divided into three groups of NASM corrective exercises, Pilates exercises and control. The two intervention groups received corrective exercises for eight weeks, the angle of lordosis was measured prior to and following the intervention, and the analysis of variance was used at a significant level of P<0.05. Results: The results showed that both 8-week corrective NASM (P=0.03) and 8-week Pilates exercises (P=0.01) had a significant effect on the angle of lumbar lordosis. However, no significant differences were observed in the control group in this regard (P=0.7). Moreover, according to ANOVA test, there were no significant differences among the three groups regarding lordosis angle prior to the intervention (P=0.13 and F=2.14). Conclusion: Based on the results of the present study, the lumbar lordosis angle decreased in both NASM and Pilates exercises groups following the intervention, with NASM exercises resulting in more reduction in the lumbar curvature compared with Pilates exercises. Therefore, therapists and experts of corrective movements can make use of these exercises as novel approaches to correcting lordosis.